An Absolute Impossibility or a Mistake from the Past? Emilia Pardo Bazán and Prudencio Canitrot - Gegúndez López, Carlos (Madrygal. Revista de Estudios Gallegos, 2016)
This article reflects on the relationship between Emilia Pardo Bazán and Prudencio Canitrot. Although ideological differences and tensions between them are evident, both writers were close friends who kept in contact in Galicia and Madrid.